Pterostilbene Inhibits the Melanogenesis Activity in UVB-Irradiated B164A5 Cells - Dayang Fredalina Basri; Leong Chen Lew; Raveena Vaidheswary Muralitharan; Tava Shelan Nagapan; Ahmad Rohi Ghazali (SAGE Publishing, 2021)
Pterostilbene is a potent antioxidant and anti-inflammatory agent. However, its chemopreventive effects via anti-tyrosinase activity and inhibitory effects on melanin content have not been reported previously. Hence, this study aimed to investigate the anti-melanogenic activity of pterostilbene on UVB-irradiated B164A5 mouse melanoma cells. The effects of pterostilbene and resveratrol on cell viability were determined by MTT assay, whereas melanin content and tyrosinase assay were employed to assess melanogenesis activity. Western blot analysis was performed to determine the tyrosinase expression. Based on the MTT assay, the IC 50 value of pterostilbene on UVB-irradiated B164A5 cells was 34.0 ± 3.43 μM, in comparison to resveratrol (>100 μM). Next, 5 and 10 μM pterostilbene showed a significant dose-dependent inhibition ( P < .01) of tyrosinase activity in UVB-irradiated B164A5 cells at 37.14 ± 2.71% and 58.36 ± 6.8%, respectively. The findings from the tyrosinase assay also confirmed the downregulation of tyrosinase expression in UVB-irradiated B164A5 cells as measured by Western blot analysis. Finally, 10 μM pterostilbene showed a significantly decreased melanin content ( P < .01) in UVB-irradiated B164A5 cells, at 27.34 ± .98 μg/mL. In conclusion, pterostilbene showed anti-melanogenic activity that was 10 times more potent than resveratrol in the UVB-irradiated B164A5 cell.